Modelación del transporte y dispersión de contaminantes atmosféricos (PM2.5 Y NOX) emitidos por FISHCORP en la ciudad de Jaramijó – 2021 - Loor Patiño, Martín Elías (2023)
The objective of this investigation was to predict the concentration of PM 2.5 and NOx at ground level from the emission source data of the company Fishcorp S.A and the climatic and topographic conditions in Jaramijó. To estimate the behavior of the pollutants emitted by Fishcorp S.A., a meteorological and climatological database was compiled from the airport weather station, to apply the Gaussian model to predict their dispersion using the AERMOND VIEW program. The results showed that the dispersion model designed through the AERMOND VIEW software was efficient for the pollutants monitored, having maximum concentrations of 1333 ug/m3 NOx and 1689 of PM 2.5 of the modeling where approximately the data measured with the calibrator that were of 1335 ug/m3 NOx and 1200 PM 2.5, being considered higher than the maximum permissible limit of Annex 4 of the TULSMA.